Hongos Nematófagos de El Salvador - Búcaro, Rosa Delia (Revista de Biología Tropical, 1983)
Eighteen species of nematophagous fungi, representing ten genera, were found in thirty-eight samples of soil collected in El Salvador. Eleven of the species were predators and seven were endozoic parasites. The numbers of nematophagous fungi found in cultivated and uncultivated soils were not significantly different. Stylopage hadra was the dominant species in the sampling. The ability to capture nematodes was previously unknown for Helicosporina veronae. One predatory species of Dactylella with conidial appendages was observed.